Applications of conceptual metaphor in the poem “Transformation” (from the poetry of Aqqab Belkheir) - bouchelaleg, kamel; saadallah, chahra (El Omda in Linguistics and Discourse Analysis, 2025)
This study focuses on one of the most important fields of cognitive linguistics, namely conceptual metaphor, which is considered one of the modern tools for analyzing poetic texts. It is based on metaphorical mappings between conceptual domains within the poetic text, starting from the source domain and projecting it onto the target domain. We have focused on this type of metaphor due to its frequent occurrence in the poetry of the poet Aqqab Belkheir, in order to reveal the extent to which his poetry lends itself to such an analysis, and to examine how the poet employs different types of conceptual metaphor in his work, thereby bringing his poetic experience closer to the reader.